Artificial Intelligence in HRM: Threat or Opportunity for Employee Engagement? - Ida Bagus Udayana Putra; Made Setini; Ida Bagus Nyoman Udayana; Mochamad Soelton; Olivia Imaculada do Rêgo Sarmento (AIBPM Publisher, 2026)
Digital transformation in human resource management encourages universities to adopt an artificial intelligence-based human resource management (AI-based HRM) system to improve the efficiency and quality of organizational governance. However, the application of AI technology in HRM functions often raises ambivalence among lecturers and education staff, because on the one hand it provides ease of work, but on the other hand it raises concerns related to the burden of adaptation and shift in work roles. This condition has the potential to affect the level of employee engagement, which is an important factor in maintaining the performance and sustainability of higher education institutions. This study aims to analyze the influence of AI-based HRM and organizational support on employee engagement with AI perception as a mediation variable. This study uses a quantitative approach with an explanatory design. Data was collected through an online questionnaire using the Likert scale from 250 respondents consisting of lecturers and education staff at universities who have implemented an AI-based e-HRM system. The data analysis technique used Partial Least Squares–Structural Equation Modeling (PLS-SEM) to test the validity, reliability, and relationships between variables in the research model. The results showed that AI-based HRM and organizational support has a positive and significant effect on employee engagement. These two variables also have a significant effect on AI perception. Furthermore, AI perception has been shown to have a direct effect on employee engagement and partially mediates the influence of AI-based HRM and organizational support on employee engagement. These findings indicate that employee perception of AI as an opportunity, not a threat, is a crucial psychological mechanism in increasing work attachment. Theoretically, this research strengthens the relevance of this studySocial Exchange Theory, Organizational Support Theory, Technology Acceptance Model, and Job Demands–Resources Theory in the context of HRM digitalization in higher education. Practically, this study emphasizes the importance of the human-centered digitalization approach so that the implementation of AI can improve the quality of work and employee engagement in a sustainable manner